Switchable photovoltaic windows enabled by reversible photothermal complex dissociation from methylammonium lead iodide. Issue 1 (December 2017) - Wheeler, Lance; Moore, David; Ihly, Rachelle; Stanton, Noah; Miller, Elisa; Tenent, Robert; Blackburn, Jeffrey; Neale, Nathan
Abstract Materials with switchable absorption properties have been widely used for smart window applications to reduce energy consumption and enhance occupant comfort in buildings. In this work, we combine the benefits of smart windows with energy conversion by producing a photovoltaic device with a switchable absorber layer that dynamically responds to sunlight. Upon illumination, photothermal heating switches the absorber layer—composed of a metal halide perovskite-methylamine complex—from a transparent state (68% visible transmittance) to an absorbing, photovoltaic colored state (less than 3% visible transmittance) due to dissociation of methylamine. After cooling, the methylamine complex is re-formed, returning the absorber layer to the transparent state in which the device acts as a window to visible light. The thermodynamics of switching and performance of the device are described. This work validates a photovoltaic window technology that circumvents the fundamental tradeoff between efficient solar conversion and high visible light transmittance that limits conventional semitransparent PV window designs. Conventional smart windows with tunable transparency are based on electrochromic systems that consumes energy. Here Wheeler et al. demonstrate a halide perovskite based photo-switchable window that dynamically responds to sunlight and change colors via reversible phase transitions.